Sms Ceria Program (Senam Mata Sehat Cerdas Kombinasi Relaksasi) for Overcoming Computer Vision Syndrome (Cvs) in Elementary School Student - Yogik Setia Anggreini; Y. Kambu Y. kambu; Ivony Fn Putriningtyas (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2023)
ABSTRACT During the COVID-19 pandemic, children in school base exposed to more gadgets than 2-3 hours/per day. Position less body good moment using gadgets, poor intensity lighting good so will harm the eye's health. The purpose of the service program Public is to increase the independence of students in doing eye exercises and a combination of relaxation, knowledge, and eye health for Overcoming Computer Vision Syndrome (CVS) for Elementary School Children. devotion Public This approach is participatory and active by sustainable. The activity consists of educating teachers and students about essential health eyes and impact CVS, giving eye exercise training to teachers and students, evaluating skills and knowledge, and advocating a party school for regulation does eye exercises combination applied relaxation routine at school. Monitoring and evaluation with the use of questionnaires and carrying out monitoring and evaluation with the use of questionnaires and sheets observation. Activity will be held for two months, starting from March until the moon of May 2022, at Inpres 25 Elementary School, Sorong City. The audience target for this activity is teachers and school students based in district Push, as many as 46 people. The results of this community service show that the average score of knowledge about eye health increased by 28.5 points, and the average eye health score increased by 8.5 points. After education, average grade knowledge, and eye health increase, participants could do eye exercises with combination relaxation independently. Empowerment Public in health eyes on children's school needs to be carried out by the government city push. We hope that the next community service can be focused on improving eye health in school children.  Keywords: Eye Exercises, Elementary School, Covid-19